150k views
2 votes
A square root function, that is stretched by a factor of 3, and shifted 4 units left and 6 units up.

1 Answer

5 votes

Answer:

The square root function will turn to;

y = 3 √(x + 4) + 6

Explanation:

Let the square root function be ;

y = √x

Now, let’s stretch this by a factor of 3

This means we are dilating by a factor of 3

Mathematically, this will be

y = 3 * √x = 3 √x

Shifting this 4 units up means that we are extending the x-axis value by 4 units

That will be ;

y = 3 √x + 4)

Now shifting this 6 units up, we finally will have;

y = 3 √(x + 4) + 6

User Pacreely
by
4.5k points